PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION MUSLIM LOZY HIJAB - Rahmatillah, Suci; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2023)
The Muslim fashion trend is growing and expanding to various levels of society. This study aims to examine the effect of celebrity endorser and brand image to purchasing decision for fashion muslim product by Lozy Hijab. Population of this study is Surabaya teenagers aged 15-35 years old and have bought or custumer of Lozy Hijab. This study used quantitative approach methode with using likert scale as measurement and multiple linear regression analysis techniques. Based on T test and F test that has been done shows that celebrity endorser and brand image partially and simultaneously have a significant effer on consumer purchasing decision. Besed on th coefficient of determination R2 shows that the variables of celebrity endorser and brand image have an influence of 31,4% on the consumer purchasing decision.